Shanghai : a novel [large type] - Kanon, Joseph (Thorndike Press large print high octane., 2024)
"After the violence of Kristallnacht, European Jews now desperate to emigrate, found the consular doors of the world closed to them. Only one port required no entry visa: Shanghai, a Western trading enclave in what was technically Chinese territory, a political anomaly that became an escape hatch if you were lucky enough to afford a ticket on one of the liners. Daniel Lohr was one of the lucky ones. But even lucky refugees have to confront the reality of Shanghai. Daniel finds himself ensnared in a maze where politics and crime are two sides of the same shiny coin. The trick is to stay one step ahead. But how do you stay ahead of murder? How do you outrun your own past?"--